Determınatıon Of Ideal Norms Of Dental Arch, Cortıcal And Apıcal Base Wıdths In Adult Turkısh Populatıon - Tancan Uysal; Zafer Sarı (Galenos Yayinevi, 2003)
The aims of this study are 1. To establish the ideal transversal norms of dental arch, cortical and apical bone base widths for orthodontic diagnosis and treatment planning using adult dental models, 2. To determine any existing gender differences between these norms and 3. To determine the relationships among investigated transversal dimensions. Dental models obtained from 150 patients (78 women and 72 men) with ideal occlusion and the well-balanced facial proportions consisted of the materials of this study. From the dental casts 6 parameters for dental arch width, 12 parameters for cortical and apical base widths were measured. Data were analyzed using descriptive statistics, independent sample t test and Pearson correlation analysis on computer with SPSS package program. Using the obtained data, transverse dimensional model norms for adult Turkish population were determined. These findings were compared with previous findings from similar studies. Normative values were formed for adult man and woman subjects separately. For upper and lower jaws, statistically significant gender differences were found between men and women. In all of both jaw findings it was determined that men's transversal width dimensions were found higher than women's. Statistically significant correlations were determined among all investigated parameters (p<0.01). Upper intermolar width and lower intermolar width showed the highest (0,869), ÜAC-C and AAC-C widths showed the lowest correlation (0,439) between two jaws.